Safe encounters : how women can say yes to pleasure and no to unsafe sex - Whipple, Beverly 4 0 16; Ogden, Gina.; 5 (New York : McGraw-Hill Book Company, 1989)
Provides information and guidance for women in the wake of the AIDS epidemic.
Includes index.
Bibliography: p. 212-215.
Booklist
Adult
Keywords: 2 -- 0; 6; Sexual behavior. -- Sex education.;Women; 20; 2